Local Government’s Tax Practices From A Cooperative Federalism Perspective - Dhungana, Raj Kumar; Acharya, Keshav K. (Nepal Public Policy Review, 2021)
This study analyses intergovernmental revenue policies and its practices in Nepal, specifically focusing on the role of local governments (LGs) in tax administration. Both qualitative and quantitative data were used in this study that concluded LGs are gradually institutionalising internal revenue bases, and rates at the local level. The constitution 2015 has provisioned that the local governments can autonomously execute various functions including legislative, administrative, financial management, tax administration and so on. Nonetheless, imperfect experience, inadequate technical skills, limited legal and procedural grounds, and weak institutional capacity, LGs are collecting tax. Result shows tax enforcement process has been implemented with limited consultation with the taxpayers and minimal coordination with the provincial and federal government. This has created number of criticisms to the LGs about their unaccountability to the taxpaying citizens. Thus, some recommendations such as integration of technical management capacity with local, provincial, and federal level for efficient fiscal administration systems; and digitization and automation of taxation for intergovernmental cooperation have been provided for improving local economic and effective tax administration at the local level.